Drug and Chemical Poisoning Patterns in Makkah Region, Saudi Arabia - Alnasser, Sulaiman Mohammed (Drug Research, 2021)
This research reveals that drugs and chemicals poisoning have been reported to have severe and fetal side effects on health provided by doctors in statistics and periodical records. This work aimed to explore the interaction among drug and chemical poisoning patterns concerning risk factors, especially gender, age, exposure circumstances, and outcomes in the Makkah region. A retrospective analysis was of clinical drug and chemical poisoning cases (2014–2015). The data were retrieved from the Department of Environmental and Occupational Health, Ministry of Health, Makkah, Saudi Arabia. The Saudi Arabia Ministry of Health received 1216 reports of drug and chemical poisoning during 2014–2015 in Makkah. This study has found that, the most affected gender was that of males (65%). The most affected age category with drug poisoning was over 15 years old (67%), but under 5 years for chemical poisoning (60%). The majority of drug poisoning cases are unknown drugs (42%), which accidental poisoning was a minority compared with other drug causes (27%). Chemical poisoning accidents were the majority causes of the recorded cases (63%). We reported healthy recovered without complications for most patients from drug and chemical poisoning (85–95%). Antidotes were administered in only (5%) of cases, and fatalities were reported (0.5% of cases). We have shown a flagrant increase in the number of people poisoned by drugs and chemical agents during 2015. Increases poisoning cases involved both genders and all studied age categories, especially males over 15 years up to 25 (drugs) and < 5 years (chemicals). Most cases were accidental (chemicals) and reported healthy recovery for most patients.
Keywords: Drug poisoning; Chemicals; Pattern; Makkah; healthy recovery; Occupational Health